1983
DOI: 10.1212/wnl.33.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of muscle function in acid maltase deficiency by high‐protein therapy

Abstract: Progressive muscle weakness in acid maltase deficiency (AMD) is associated with intralysosomal accumulation of glycogen and altered myofibrillar morphology. A rapid fall in circulating branched chain amino acids after protein ingestion in a child with AMD suggested that increased net muscle protein catabolism may play a part in the pathogenesis of this condition. To reduce this muscle catabolism, the patient was treated with a high-protein diet for 12 months. This has reversed the weakness and wasting, with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 0 publications
2
47
0
2
Order By: Relevance
“…For patients with late-onset Pompe disease, the goal is intended to manage 1) the increasing accumulation of glycogen and 2) the increase in amino acid utilization 7,11. Slonim et al63,64 have observed that a high protein-low carbohydrate diet plus aerobic exercise, can be beneficial to some of these patients (see cautions on limits of exercise in the Musculoskeletal/Functional/Rehabilitation section).…”
Section: Gastrointestinal/nutritionmentioning
confidence: 99%
“…For patients with late-onset Pompe disease, the goal is intended to manage 1) the increasing accumulation of glycogen and 2) the increase in amino acid utilization 7,11. Slonim et al63,64 have observed that a high protein-low carbohydrate diet plus aerobic exercise, can be beneficial to some of these patients (see cautions on limits of exercise in the Musculoskeletal/Functional/Rehabilitation section).…”
Section: Gastrointestinal/nutritionmentioning
confidence: 99%
“…2,3 This hypothesis derives from the observation that the severity of myopathy seems to be out of proportion to the degree of glycogen muscle deposition. 13 Studies on plasma amino acid levels after ingestion of a protein load, and studies with leucine and alanine isotope turnover, support this view. 3 The restoration of normal levels of serum proteins in our patient could indicate that protein wasting, one of the main mechanisms of muscle damage, is reversed by ERT.…”
Section: Discussionmentioning
confidence: 97%
“…In patients in the early stages of this disease, both alanine and glutamine levels in plasma are very reduced. This has prompted attempts with high-protein, low-carbohydrate diets as well as supplements of alanine to attempt to correct these abnormalities (Bodamer et al 1997(Bodamer et al , 2000(Bodamer et al , 2002Slonim et al 1983). Although there have been sporadic reports suggesting potential benefit from these dietary strategies, there have, as yet, been no conclusive studies that are associated with consistent benefit to these patients.…”
Section: Pyruvate Carboxylase (Pc) Deficiency (Type B)mentioning
confidence: 99%